Peningkatan Efektivitas Pembelajaran Melalui Kepemimpinan Instruksional Dan Budaya Sekolah - Rinaldi, Aprian; Sarimanah, Eri; Suharyati, Henny (Universitas Pakuan, 2023)
INCREASED LEARNING EFFECTIVENESS THROUGH INSTRUCTIONAL LEADERSHIP AND SCHOOL CULTUREThis study aims to find efforts to improve learning effectiveness through the study of the relationship between instructional leadership and school culture. This study used quantitative research methods with correlational techniques. This research was carried out on permanent foundation teachers at Private Vocational Schools located in Caringin District, Cigombong, Cijeruk, Bogor Regency totaling 26 schools. Sampling using the proportional random sampling technique amounted to 135 from 203 populations. Hypothesis testing was performed at a significance level of 0.05. The results showed that: 1) there was a very significant positive relationship between instructional leadership and learning effectiveness, with a correlation coefficient score ry1 = 0.414; 2) there is a very significant positive relationship between school culture and learning effectiveness because a large correlation coefficient score ry2 = 0.286 was obtained; and (3) there was a very significant positive relationship between instructional leadership and school culture together with learning effectiveness, correlation coefficient score ry12 = 0.451. Based on the results of the study the effectiveness of learning will increase if there are efforts to improve the principal's instructional leadership and school culture.